Desenvolvimento de uma representação mesoscópica para marcadores fluorescentes em DNA e predição de intensidade de fluorescência - Pâmella Miranda de Moura (2020)
Fluorescent dyes attached to DNA molecules are used in biomedicine and biotechnology areas, for example, and they can be studied with mesoscopic models such as Peyrard-Bishop model (PB). In particular, Cy3 and Cy5 dyes showed a great efficiency and good results in their performance, also they provide a higher stability to DNA molecule. In our work, we optimized the parameter for Morse potentials that represents the hydrogen bonding, and a harmonic potential that represents the stacking interaction for DNA duplexes attached to Cy3 and Cy5. Using an experimental melting temperatures set, collected from the literature, for this combination of DNA+Cy3/Cy5, we applied the PB mesoscopic model to describe these parameters. The PB model is a statistical physics model that allows us to obtain some properties of the DNA molecule, by calculating the canonical partition function. Our results for Cy3 and Cy5 show values which are similar to AT base pair in DNA. This confirms that Cy3 and Cy5 links to DNA like an extra base pair, as was suggested from nuclear magnetic resonance measurements. Another problem that we dealt with was the question if the mesoscopic model could serve as predictor for fluorescence intensity of Cy3 and Cy5 in DNA. To this end, we used another dataset of microarray intensities related to Cy3 and Cy5 coupled at 5' terminal of the DNA molecule. The set consists of 1024 DNA sequences, synthesized in an uniform way, with fluorescence intensity data. We calculated the displacement of base pairs in the direction of hydrogen bonds, called average opening, that characterizes the denaturation process of DNA double helix. The values obtained for this displacement were correlated to fluorescence intensities. We correlated these data to average openings for varied conditions and different parameters, and we found a high correlation. Then we developed a program to maximize the correlation varying the mesoscopic model parameters. The results obtained for the denaturation temperatures parametrization and the high correlation for fluorescence intensities show that the mesoscopic model is an appropriate tool to optimize DNA probes.